"NGAPATI" DALAM TRADISI MASYARAKAT BANYUURIP Studi Living Hadits - Hasan Su'adi (Jurnal Penelitian, 2015)
This study is intended to determine the understanding of Banyuurip society leaders towards human creation hadith and other hadiths pertaining to Ngapati tradition and to know its implementation on Ngapati tradition among Banyuuripsociety in Pekalongan city. This qualitative study uses interview, observation and documentation to collect and interprete data. This study concludes that 1) the tradition is in line with Islamic teachings (hadith) according to Banyuurip society leaders and 2) society makes creation towards hadith texts, then implemented in the form of action in this case is Ngapati tradition.